Legal Certainty in the Execution of Mortgage Rights for the Settlement of Non-Performing Loans - Atika Sandra Dewi; Rianmahardhika Sahid Budiharseno (Lex Publica, 2026)
Legal certainty in the execution of Mortgage Rights is essential for protecting creditors and ensuring the effective resolution of non-performing loans (NPLs) in Indonesia. Although Law No. 4 of 1996 concerning Mortgage Rights (UUHT) provides a comprehensive legal framework for secured lending, its implementation continues to encounter significant legal and institutional challenges. This study aims to examine the extent to which the existing legal framework ensures legal certainty, identify the doctrinal, procedural, and institutional barriers affecting Mortgage Rights execution, and propose legal reforms to improve its effectiveness. The research employs normative legal research using statutory, conceptual, and case approaches. Legal materials were collected through library research and analyzed qualitatively using statutory interpretation, comparative analysis, and source triangulation. The findings indicate that the UUHT establishes a coherent framework through the principles of speciality, publicity, droit de préférence, and droit de suite, supported by executorial title, parate executie, and private sale mechanisms. However, inconsistent judicial interpretation, procedural complexity, fragmented institutional coordination, and incomplete digital implementation continue to undermine effective execution and legal certainty. As the principal contribution, this study proposes an Integrated Legal Certainty Model that combines normative harmonization, judicial consistency, institutional coordination, digital mortgage integration, and balanced creditor-debtor protection.